2015
DOI: 10.1186/s40880-015-0015-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus reactivation and hepatitis in diffuse large B-cell lymphoma patients with resolved hepatitis B receiving rituximab-containing chemotherapy: risk factors and survival

Abstract: IntroductionHepatitis B virus (HBV) reactivation has been reported in B-cell lymphoma patients with resolved hepatitis B (hepatitis B surface antigen [HBsAg]-negative and hepatitis B core antibody [HBcAb]-positive). This study aimed to assess HBV reactivation and hepatitis occurrence in diffuse large B-cell lymphoma (DLBCL) patients with resolved hepatitis B receiving rituximab-containing chemotherapy compared with HBsAg-negative/HBcAb-negative patients to identify risk factors for HBV reactivation and hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…However, the American Society of Clinical Oncology recommended screening for patients who were at high risk for HBV infection and for those receiving highly suppressive chemotherapy regimens such as hematopoietic stem cell transplantation and rituximab‐based therapy before any forms of chemotherapy . According to previously published studies, the reactivation risk ranged from 6% to 10% for patients with HBV infections when they were receiving rituximab‐based chemotherapy . Our study demonstrated a higher reactivation rate with some types of high‐risk regimens for the treatment of NPC.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the American Society of Clinical Oncology recommended screening for patients who were at high risk for HBV infection and for those receiving highly suppressive chemotherapy regimens such as hematopoietic stem cell transplantation and rituximab‐based therapy before any forms of chemotherapy . According to previously published studies, the reactivation risk ranged from 6% to 10% for patients with HBV infections when they were receiving rituximab‐based chemotherapy . Our study demonstrated a higher reactivation rate with some types of high‐risk regimens for the treatment of NPC.…”
Section: Discussionmentioning
confidence: 55%
“…11 According to previously published studies, the reactivation risk ranged from 6% to 10% for patients with HBV infections when they were receiving rituximab-based chemotherapy. [19][20][21] Our study demonstrated a higher reactivation rate with some types of high-risk regimens for the treatment of NPC. In addition, the American Gastroenterological Association recently published guidelines on the management of HBV reactivation, 22 and they defined high-risk patients as those with a reactivation risk exceeding 10% or those positive for HBsAg and receiving anthracycline-based chemotherapy.…”
Section: Discussionmentioning
confidence: 62%
“…A positive anti‐HBs versus only anti‐HBc reduced reactivation with a pooled OR of 0.21 (95% CI 0.14‐0.32) (Fig. ) . The regression test for funnel plot asymmetry was not significant ( P = 0.84).…”
Section: Resultsmentioning
confidence: 95%
“…). Of the 19 observational studies, 11 were prospective and eight were retrospective . One RCT compared entecavir HBV prophylaxis (before chemotherapy) versus entecavir treatment for HBV reactivation …”
Section: Resultsmentioning
confidence: 99%
“…One factor is lymphomagenesis which provides a milieu of immunosuppression which favors HBV replication. In addition (50,51), when immunosuppressive agents are initiated in lymphoma, induced immunosuppression triggers viral replication that manifests as HBV reactivation (38,(52)(53)(54). It is important to note that spontaneous reactivation can occur in individuals without lymphoma, especially individuals with positive HBeAg, likewise coinfection with HIV, bacterial infections or stressors (emotional and physical) (55).…”
Section: Hbv In Lymphoma Patientsmentioning
confidence: 99%